Kad Hari Raya - Sallehudin, Ahmad; Khanoon, Faridah; Ahmad, Azan; Ahmad, Ann; Ahmad, Lena; Ahmad, Fhamy; Ahmad, Fauzy; Ahmad, Feizal (Nil, 1975)
Kad ucapan hari raya yang diutuskan kepada Profesor Diraja Ungku Abdul Aziz daripada Ahmad Sallehudin, Faridah Khanoon, Azan, Ann, Lena, Fhamy, Fauzy, Feizal, Farouk & Firdouz